Development platform for UV-NIL processes using polymer masters produced by laser ablation and photolithography - Joachim Zajadacz; Pierre Lorenz; Martin Ehrhardt; Klaus Zimmer (Nanotechnology and Precision Engineering)
Ultraviolet nanoimprint lithography (UV-NIL) is a versatile and cost-effective technique for the fabrication of micro- and nanostructures by copying master patterns in a planar or a roll-to-roll process through curing of a liquid UV-sensitive precursor. For applications with a high pattern complexity, new UV-NIL process chains must be specified. Master fabrication is a challenging part of the development and often cannot be accomplished using a single master fabrication technique. Therefore, an approach combining different patterning fabrication techniques is developed here for polymer masters using laser direct writing and photolithography. The polymer masters produced in this way are molded into inverse silicone stamps that are used for roll-to-roll replication into an acrylate formulation. To fit the required roller size for large-area UV-NIL, several submasters with micrometer-sized dot and line gratings and prism arrays, which have been patterned by these different techniques, are assembled to final size of ∼200 × 600 mm2 with an absolute precision of better than 50 µm. The size of the submasters allows the use of standard laboratory equipment for patterning and direct writing, thus enabling the fabrication of micro- and even nanostructures when electron-beam writing is utilized. In this way, the effort, time, and costs for the fabrication of masters for UV-NIL processes are reduced, enabling further development for particular structures and applications. Using this approach, patterns fabricated with different laboratory tools are finally replicated by UV-NIL in an acrylate formulation, demonstrating the high quality of the whole process chain.